Volker Seresse: Des Königs »arme weit abgelegenne Vntterthanen«. Oesel unter dänischer Herrschaft 1559/84-1613. (Peter Lang Verlag, 1996). 296 s., 84 DM. - Steen Jensen, Jørgen (Historie/Jyske Samlinger, 1999)
-